Developing Muslim Tourist Satisfaction Through Their Sense of Community - Amalia, Fatya Alty; Sumarjan, Norzuwana; Suhartanto, Dwi (Jurnal Internasional Penelitian Bisnis Terapan, 2024)
The significance of ensuring Muslim tourist satisfaction in fostering loyalty motivates scholars to explore additional influencing factors. This study investigates how a sense of community impacts tourist satisfaction in halal destinations within Muslim-majority countries. By analyzing responses from 306 Muslim tourists from Indonesia and Malaysia using partial least squares (PLS), the findings reveal that specific dimensions of a sense of community—specifically, membership and needs fulfilment—significantly enhance tourist satisfaction. Conversely, the dimensions of influence and shared emotional connection do not significantly impact satisfaction. Moreover, the strength of the relationship between a sense of community and tourist satisfaction varies between Indonesian and Malaysian tourists. This study contributes both practically and theoretically to the tourism sector.